Roles of non-specific lipid transfer proteins in plant defense: structural and functional perspectives - McLaughlin, John E.; Tumer, Nilgun E. (Frontiers in Fungal Biology, 2025)
Non-specific lipid transfer proteins (nsLTPs) are vital and versatile components of plant cellular systems. They are characterized by a conserved eight-cysteine motif and are increasingly recognized for their dual roles in direct defense and stress modulation. nsLTPs serve critical structural and signaling functions in plant immunity. In contrast, other lipid transfer proteins, which lack the conserved cysteine motif, are primarily localized at membrane contact sites, specialized inter-organelle junctions that act as central hubs for lipid trafficking and signaling. This review explores the diverse roles of nsLTPs from structural, functional, and evolutionary perspectives, and examines current classification methodologies for the plant nsLTP superfamily. Functionally, nsLTPs contribute to the formation of protective barriers by transporting cutin monomers and other lipids, while also possessing lipid-specific antimicrobial properties that disrupt pathogen membranes. They support redox balance by scavenging reactive oxygen species, thereby minimizing oxidative stress. Additionally, nsLTPs are involved in defense signaling by transporting lipid-derived molecules essential to systemic acquired resistance. Their structural adaptability enables binding to a wide range of lipid species, underpinning their involvement in cuticle integrity, immune responses, and abiotic stress tolerance. These attributes position nsLTPs as promising targets for engineering durable, broad-spectrum disease resistance in crops. However, significant knowledge gaps remain regarding their structure-function relationships, lipid transport mechanisms, and roles in defense signaling and pathogen resistance. Addressing these challenges through advanced molecular and genetic tools could unlock the potential of nsLTPs to enhance crop resilience and contribute significantly to global food security.